2004
DOI: 10.1002/syn.20077
|View full text |Cite
|
Sign up to set email alerts
|

Metyrapone attenuates the sequential learning deficits but not monoamine depletions following d,l‐fenfluramine administration to adult rats

Abstract: Fenfluramine (FEN) is a substituted amphetamine known for its anorectic effects, without the stimulatory or abuse potential associated with other amphetamine derivatives. FEN is a potent serotonin (5-HT) releaser and reuptake inhibitor and has been shown to cause depletions of 5-HT that can last days and even weeks after administration. Administration of FEN four times on a single day also causes a prolonged increase of corticosterone (CORT) that lasts approximately 72 h following the first FEN dose. This dosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 31 publications
3
20
0
Order By: Relevance
“…Interestingly, the path integration task used in this experiment, the CWM, is more sensitive at detecting detrimental effects of several substituted amphetamines in adult rats than the MWM (Able et al, 2006;Skelton et al, 2004;Williams et al, 2002) and the present results are consistent with that pattern. Comparable to the administration of fenfluramine, a potent 5-HT releaser, 5-MEO-DIPT (1) produced hypothermia during drug administration, (2) stimulated the adrenal function of the animals as demonstrated by the increased levels of CORT 3 days after drug administration and an increase in adrenal weights, and (3) disrupted CWM performance while sparing MWM performance (cf, Skelton et al, 2004;Williams et al, 2001;Williams et al, 2002). Unlike fenfluramine, 5-MEO-DIPT produced no decrease in 5-HT or 5-HIAA (Skelton et al, 2004).…”
Section: Effects Of 5-meo-diptsupporting
confidence: 88%
See 4 more Smart Citations
“…Interestingly, the path integration task used in this experiment, the CWM, is more sensitive at detecting detrimental effects of several substituted amphetamines in adult rats than the MWM (Able et al, 2006;Skelton et al, 2004;Williams et al, 2002) and the present results are consistent with that pattern. Comparable to the administration of fenfluramine, a potent 5-HT releaser, 5-MEO-DIPT (1) produced hypothermia during drug administration, (2) stimulated the adrenal function of the animals as demonstrated by the increased levels of CORT 3 days after drug administration and an increase in adrenal weights, and (3) disrupted CWM performance while sparing MWM performance (cf, Skelton et al, 2004;Williams et al, 2001;Williams et al, 2002). Unlike fenfluramine, 5-MEO-DIPT produced no decrease in 5-HT or 5-HIAA (Skelton et al, 2004).…”
Section: Effects Of 5-meo-diptsupporting
confidence: 88%
“…All tests were performed during the light phase of the light/dark cycle. This order of testing closely follows one that we have used to assess the impact of a single day exposure to other psychostimulants in adult animals (Cohen et al, 2005;Skelton et al, 2004;Williams et al, 2002). We have previously shown that the order of the CWM and MWM does not significantly affect the outcome with these compounds (Williams et al, 2002).…”
Section: Methodsmentioning
confidence: 77%
See 3 more Smart Citations